Realizing a Waste-Free Dream Entering the Era of Society 5.0 Towards a Smart City in Manado City - Ai, Nio Song; Lumban Raja, Grace Ega Yulianti; Marfuah, Siti; Tumoka, Karina Preyse (Program Studi Di Luar Kampus Utama Universitas Pattimura, 2021)
Waste management in Manado City is still ineffective because it does not use environmentally and friendly waste management methods and techniques that can disrupt health and disrupt environmental sustainability. This scientific work aims to provide solutions in handling waste problems in the city of Manado in fulfilling the dream of zero waste entering the era of Society 5.0 towards a Smart City which is in accordance with the goals of Sustainable Development Goals (SDG's). The promising idea for the waste problem in the city of Manado is converting organic and inorganic waste into renewable energy in a small scale which can be developed further into a larger scale (industry).This idea can support Manado City in bringing to a reality of a smart city because the inhibitants are equipped with education (knowledge) and technology. Futuristic waste management with a combination of technology and education in Manado City towards a smart city is one of the effective innovations to process waste with simple technology that utilizes both organic and inorganic waste. This combination will be able to result in renewable energy in the form of biofuels using pyrolisis techniques. Pyrolysis is a plastic-waste-processing technique by heating plastic until the temperature reaches Â± 400 ËšC without oxygen and then producing a liquid oil which can be used as fuel.